(untitled) (Bangladesh Journal of Botany, 2008)
Symphytum asperum Lepechin, S. ibericum Steven and S. sylvaticum Boiss. were examined morphologically, micromorphologically and anatomically. Scanning electron microscopy was used to examine leaf surface and trichomes of these species. These species had bifacial and hypostomatous leaf types. Epidermal cells of leaves were usually polygonal or irregular in form. The pattern of anticlinical cells may vary in different species and between the upper and lower epidermis of the same species. Stomata are anisocytic and anomocytic in three species. Stomata index is 27.5 for S. sylvaticum, 24.65 for S. ibericum and 21.86 for S. asperum glandular trichomes are capitate in forms and more dense on the lower epidermis than upper epidermis. Eglandular trichomes are simple, short or long, unicellular or multicellular and thin or thick. Key words: Micromorphology, Anatomy, Symphytum DOI = 10.3329/bjb.v36i2.1496 Bangladesh J. Bot. 36(2): 93-103, 2007 (December) Â Â